Aporphinoid Alkaloids Derivatives as Selective Cholinesterases Inhibitors: Biological Evaluation and Docking Study - Cavallaro, Valeria (2020)
Alzheimer's dementia is a neurodegenerative disease that affects the elderly population and causes memory impairment and cognitive deficit. Manifestation of this disease is associated to acetylcholine decrease; thus, Cholinesterase inhibition is the main therapeutic strategy for the treatment of Alzheimer's disease. In the present study, a series of aporphinoid alkaloids were tested as potential acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitors in vitro. Alkaloids liriodenine (3) and cassythicine (10) were the best inhibitors of both cholinesterases with IC50 values lower than 10 μM. In addition, these alkaloids demonstrated better inhibition of BChE than reference drug galantamine. In addition, some alkaloids showed selective inhibition. Laurotetatine clorhydrate (13) selectively inhibit AChE over BChE. On the contrary, pachyconfine (7) interacted more efficiently with BChE active site. Molecular modelling studies were performed in order to illustrate key interactions between most active compounds and the enzymes and to explain their selectivity. These studies reveal that the benzodioxole moiety exhibits strong interactions due to hydrogen bonds that form with the Glu201 (AChE) and Tyr440 (BChE) residues, which is reflected in the IC50 values.